Subaortic Membrane Papillary Fibroelastoma - Robyn Bryde; Kevin Landolfo; Jordan C. Ray; Pragnesh Parikh; Qihui “Jim” Zhai; Carolyn Landolfo (Case Reports in Cardiology)
A 61-year-old male presented for an annual exam and received a transthoracic echocardiogram (TTE) which revealed a mobile mass arising from a subaortic membrane. Further investigations with a transesophageal echocardiogram (TEE) and cardiac computerized tomography angiography (CTA) confirmed the presence of a mobile 9 mm×3 mm mass on a subaortic membrane. Cardiothoracic surgery was performed with an open operation removing the mass and subaortic membrane. Upon visual inspection, the mass was likened to a sea anemone and immunohistochemical staining performed pathologically confirmed the diagnosis of cardiac papillary fibroelastoma. This case represents the first reported example of a cardiac papillary fibroelastoma (PFE) arising from a subaortic membrane. Although PFEs are benign cardiac tumors, proper identification and consideration for excision of these lesions may be indicated to prevent thromboembolic complications.